Mating between Anartia jatrophae jatrophae (Linnaeus, 1763) and Ortilia liriope (Cramer, 1775) (Lepidoptera: Nymphalidae) in the Brazilian Central Amazon - Raymê dos Santos Carvalho; Gilcélia Melo Lourido; Elza Fernanda dos Santos Martins; Kelve Franklimara Sousa Cézar (Revista Chilena de Entomología)
Reproductive isolation is crucial for the survival of species in nature; nevertheless, interspecific mating and hybrid formation can still occur. In this work, we report a mating event between Anartia jatrophae jatrophae (Linnaeus) and Ortilia liriope (Cramer) (Lepidoptera: Nymphalidae). This event was observed on April 30, 2023, at the butterfly house of Museu da Amazônia (MUSA) in Manaus, Amazonas, Brazil. Although hybrid formation is not uncommon among Lepidoptera, to our knowledge, this is the first record of mating between A. j. jatrophae and O. liriope in the Brazilian Central Amazon region. This mating event between distinct species may occur due to ecological, chemical, and evolutionary factors.